Crustal stretching process denounced by mafic magmatism in the Finisterra Terrane; the yield of a back-arc basin? - Moreira, Noel (2020)
The occurrence of a new tectono-stratigraphic terrane (Finisterra Terrane), located in the westernmost domains of the Porto-Tomar-Ferreira do Alentejo Shear Zone, has been highlighted in the last few years. Nevertheless, there are several gaps in the geological knowledge of this Terrane, including the interpretation of existing data in the framework of the new tectono-stratigraphic terrane proposal, with an independent evolution from the Iberian Terrane. This work is an approach to the mafic magmatism significance that is described in the tectono-stratigraphic units from Abrantes-Tomar and Porto-Espinho-Albergaria-a-Velha sectors of the Finisterra Terrane. The geochemical data of the amphibolite rocks show affinities with mafic and ultramafic protholits with geochemical features between within-plate basalts and MORB. These amphibolites express specific geochemical features (e.g. N-MORB normalized Ba and Th enrichments, as well as Nb and Ta anomalies), suggesting their emplacement in a back-arc basin tectonic setting.